2021
DOI: 10.1186/s42836-020-00059-z
|View full text |Cite
|
Sign up to set email alerts
|

Is methylmethacrylate toxic during pregnancy and breastfeeding?--- a systematic review

Abstract: Introduction Methyl methacrylate (MMA) is commonly used in the fields of dentistry and orthopaedic surgery. However, there remain concerns for the occupational hazards of MMA, particularly during pregnancy and breastfeeding. Methods We performed a systematic review of studies on effects that MMA may have in pregnancy in the context of exposure during orthopaedic surgery and dentistry. Review articles, studies lacking statistical data, single case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A recent systematic review including animal studies across dentistry and orthopaedics concluded that the potential teratological effects of PMMA could not be excluded by existing evidence; however, the typical PMMA exposure levels appear to be substantially less than currently proposed limits. 41 A number of barriers to pregnancy were identified in our review, including the attitudes/perceptions of colleagues and TPDs, the cost of maternity leave, and the lack of formal policies on maternity leave and breastfeeding, particularly in the USA. In the UK and USA, there are now formal policies in place for doctors who are breastfeeding to be provided with the appropriate facilities for lactation, and adequate refrigerated storage for breastmilk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review including animal studies across dentistry and orthopaedics concluded that the potential teratological effects of PMMA could not be excluded by existing evidence; however, the typical PMMA exposure levels appear to be substantially less than currently proposed limits. 41 A number of barriers to pregnancy were identified in our review, including the attitudes/perceptions of colleagues and TPDs, the cost of maternity leave, and the lack of formal policies on maternity leave and breastfeeding, particularly in the USA. In the UK and USA, there are now formal policies in place for doctors who are breastfeeding to be provided with the appropriate facilities for lactation, and adequate refrigerated storage for breastmilk.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review including animal studies across dentistry and orthopaedics concluded that the potential teratological effects of PMMA could not be excluded by existing evidence; however, the typical PMMA exposure levels appear to be substantially less than currently proposed limits. 41…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of 248 female orthopaedic surgeons, 41.7% of respondents reported that they would leave the room if PMMA cement were being used while they were pregnant, and 24.7% would choose to leave the room if they were actively breastfeeding 14 . Further, although no studies have linked MMA exposure to teratogenic effects, the potential for birth defects caused by MMA cannot be excluded 3 . Although it has been shown that exposure to MMA in the operative setting does not lead to increased levels of MMA in breast milk or in serum, the concerns regarding occupational exposure to MMA are still present 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Occupational Safety and Health Administration (OSHA)permissible exposure limits of 100 ppm for an 8-hour period, these fumes are considered an occupational hazard, particularly to individuals who are pregnant 3,4 . Therefore, the reduction of MMA vapor emissions is desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation